Prenatal Islamic Education; Initial Measurements Towards Building Islamic Generation (a Case Study of Mothers in Gondang, Wonopringgo, Pekalongan) - Uswatun Khasanah (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
This study aims to: 1) obtain a clear view of the mother’s knowledge on prenatal Islamic education in Gondang, Wonopringgo, 2) obtain information on how the mothers apply the prenatal Islamic education,3) obtain information on how the fathers play their role in applying the prenatal Islamic education. This research is qualitative by using phenomenological approach. The data were collected through observation, interview, and documentation. The data analysis uses interractive analysis. The results showed that: Firstly, the concept of prenatal Islamic education mothers in Gondang, Wonopringgo, Pekalongan hold are the understanding of 1) selecting and deciding each other’s fated partner in life by considering their character and religion; 2) reciting a du’abefore sexual intercourse with their husbands (jimak); and 3) maintaining their good behavior during pregnancy by providing behavioral stimuli, such as talking to the baby, involving the baby when doing religious routine, touching their bellies, doing more dzikir, and reciting the Qur’an. Secondly, The implementations of prenatal Islamic education by mothers in Gondang, Wonopringgo, Pekalongan are 1) in the preparation phase, they select and decide eachother’s fated partner in life by considering their character and religion and involving their parents’ agreement; 2) reciting a du’abefore sexual intercourse with their husbands (jimak); 3) maintaining their good behavior during pregnancy by providing behavioral stimuli to their baby inside the womb during embryonic phase by talking to the baby, involving the baby when doing religious routine, touching their bellies, doing more dzikir, and reciting the Qur’an. The materials in implementing prenatal Islamic education this research are dzikir, Islamic songs, the Qur’an, shalawatto Prophet, noble behavior, the material for Islamic lecture, and parent’s good example.The methods employed are intending successful communication to happen with the fetus, involving the fetus in religious routines, sadaqah; meaning worshipping Allah by giving money without that being made obligatory in sharee’ah, reciting the Qur’an, listening to Islamic music, watching Hafidz al-Qur’an program, reading the stories of prophets, reciting du’a, and touching and stroking the mother’s womb. The media used are hand phones, laptops, MP3s, books, TVs, the Qur’an, halaqah (Islamic education), Posyandu; a monthly clinic for children and pregnant women, and voices from their parents and other relatives.Thirdly, Husbands in this research play important roles in the implementation of prenatal Islamic education. They commit many good deeds to show how care they are with them.